ADN Más Vida: la identidad de una iglesia postdenominacional mexicana en crecimiento = DNA Más Vida : the identity of a growing Mexican post-denominational church - Gomes, Edson Fernando (Ciencias sociales y religión, 2020)
The Christian Church “Más Vida” represents a strong exponent of emerging Christianity and postdenominationalism in Mexico. This church has found ways to conquer followers of different ages and social classes with business, technological and communication strategies mixed with their religious practices and beliefs. This article is derived from a master's research and has data obtained through interviews with members of the “Más Vida” church, on the campus of the city of Guadalajara. It presents the DNA Más Vida and with this, the origin, base, and nucleus of the identity construction of this church are explained. The results of the construction of this identity are organizational culture, a brand identity, and a symbolic tool called DNA Más Vida.